Assessing the demographics of the 2021 and 2022 CEDAR workshop - Jones, McArthur; Maute, Astrid (Frontiers in Astronomy and Space Sciences, 2022)
The Coupling, Energetics and Dynamics of Atmospheric Regions (CEDAR) community is made of engineers, scientists, physicists, and students with a mission to understand the fundamental properties and predictability of the space-atmosphere interaction region, including the mesosphere, thermosphere, ionosphere, and inner magnetosphere. At the 2020 CEDAR annual workshop, community-wide feedback received on diversity, equity, and inclusion (DEI) in CEDAR warranted a grassroots effort focused on addressing the DEI issues raised. This led to the creation of the CEDAR DEI task force, whose goals were to 1) Assess and formalize DEI efforts in CEDAR; 2) Establish and normalize a DEI presence in the CEDAR community; and 3) Foster improvement in CEDAR through implementation of actionable initiatives that promote diversity, equity, and inclusion. Of these actionable items collecting demographic information on those participating in the Annual CEDAR Workshop was identified as the top priority. This paper therefore, reports the demographic information obtained from CEDAR registrants for the virtual workshop in 2021 and in-person workshop in 2022. In general, the demographics of CEDAR are consistent with those in broader science, technology, engineering, and mathematics (STEM) fields, that is, most participants identify as male, White, and or Asian/Middle Eastern. On average, women and historically underrepresented races and ethnicities in STEM fields make up roughly 30% and 10%, respectively, of all 2021 and 2022 CEDAR Workshop registrants over the past 2 years. We further discuss the demographics of CEDAR relative to reports published in recent years by other organizations, where possible.